Psychosocial impact on families with an infant with a hypoplastic left heart syndrome during and after the interstage monitoring period – a prospective mixed‐method study. Issue 21 (14th February 2017) - Stoffel, Gaby; Spirig, Rebecca; Stiasny, Brian; Bernet, Vera; Dave, Hitendu; Knirsch, Walter
Abstract : Aims and objectives: To investigate parents' experiences, coping ability and quality of life while monitoring their sick child with hypoplastic left heart syndrome at home. Background: Interstage home monitoring for children with hypoplastic left heart syndrome reduces interstage mortality between Norwood stages I and II. Little is known about the psychosocial impact of interstage home monitoring. Design: Prospective mixed‐method study. Methods: This study assessed the psychosocial impact on parents during interstage home monitoring. This contains for quantitative assessment the Short Form Health Survey questionnaire and the Impact of Family Scale administered one and five weeks following discharge before and after stage II. For qualitative assessment, semi‐structured interviews focussing on the postdischarge coping strategies were conducted twice, five weeks after hospital discharge before and after stage II. Results: Ten infants (eight males) with hypoplastic left heart syndrome ( n  =   7) or other types of univentricular heart malformations ( n  =   3), and their parents (nine mother/father two‐parent households, one single mother) were included. There were no interstage deaths. Mental Health Composite Summary scores were low in both parents (mothers: 40·45 ± 9·07; fathers: 40·58 ± 9·69) and lowest for the item 'vitality' (mothers: 37·0 ± 19·46; fathers: 43·12 ± 25·9) before and after stage II. Impact of Family Scale values showed higher daily and social burdens for mothers. ' Becoming a family ' was the most important task as coping strategy to equilibrate the fragile emotional balance. The parents judged interstage home monitoring as a protective intervention. Conclusions: Although psychosocial burden before and after stage II remains high, becoming a family is an essential experience for parents and confirms their parenthood. Relevance to clinical practice: Healthcare professionals must be aware of parents' needs during this vulnerable interstage period and to provide psychosocial and nursing support.